Nurturing Sustainable Development: The Interplay of Parenting Styles and SDGs in Children's Development - Cristina Tripon (MDPI AG, 2024)
This study delves into the dynamics of parenting styles and their impact on the cognitive and social-affective development of children within diverse family populations, contextualized within the framework of Sustainable Development Goals (SDGs). Drawing from a sample population comprising families from various socio-economic backgrounds and cultural contexts, the research explores the nuanced interactions between parenting approaches-ranging from authoritarian/permissive to democratic-and children's developmental trajectories. By examining families with different numbers of children, this study elucidates the differential effects of parenting styles on cognitive adaptability and social-emotional skills across varying family structures. Democratic parenting emerges as a critical factor in promoting children's well-being, equitable access to education, and the fostering of peaceful societies, aligning with SDGs 3, 4, and 16. Furthermore, the research addresses disparities in child development outcomes, shedding light on issues of gender equality (SDG 5) and reduced inequalities (SDG 10) within the context of family dynamics. Through a comprehensive analysis of diverse family populations, this study underscores the significance of inclusive and nurturing parenting practices in advancing sustainable development objectives, advocating for collaborative efforts (SDG 17) to support families in fostering optimal child development outcomes for all.